Modulators of complement activation: a patent review (2008 - 2013) - Larghi, Enrique Leandro (2014)
Introduction: The architecture of the complement system has evolved during the last 600 – 700 million years to become an amazingly efficient and highly versatile alerting and cell killing device. Under physiological conditions, this system acts as a well-regulated cascade, protecting the organism against pathogens and participating during the initial defensive steps of humoral and cellular response. The unregulated activation of this system may cause or even aggravate diseases; therefore, its modulation is currently considered of high importance. Areas covered: This review is a critical examination on patent literature published between 2008 and 2013. An insight is provided about the discovery and development of novel therapeutic agents. These include macromolecules, polysaccharides and proteins, specific antibodies, and hybrid or chimeric products. Peptides and low molecular weight organic compounds (natural products, their derivatives and fully synthetic molecules) are covered as well. Expert opinion: The search of specific inhibitors of the complement cascade has become one of the Holy Grails of Medicinal Chemistry for the last 30 – 40 years, with very few cases of success. Some highly specific macromolecules are currently available as modulators of the complement. However, there is still a marked need to find new, more specific, efficient and convenient alternatives, especially suited for chronic administration, including novel inexpensive small molecule inhibitors. Analogously, despite the initial success with specific monoclonal antibodies, a vast territory is awaiting to be explored and conquered, regarding the regulation of complement activation by antibody-mediated blockage of specific polypeptides or receptor sites